What is so special about robots and trade? - María Teresa Alguacil Marí; Alessia Lo Turco; Inmaculada Martínez-Zarzoso (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2020)
We estimate the effect of the introduction of robots on the intensive and extensive margins of exports using a sample of Spanish manufacturing firms over the period 1994-2014. The empirical strategy used to identify the causal impact of robot adoption on the firm level export performance consists on combining propensity score matching (PSM) and difference in differences (DID) techniques. The results show that firms that start to use robots experience a sharp increase in their export probability, export sales and share of exports in total output and this result is robust to a wide array of checks. Robot adoption not only helps firms to start exporting and moves their specialisation towards intermediate products, but also favours export survival and export sales of exporting firms. The main results are driven by firms active in non-comparative advantage industries facing higher export sunk costs and market penetration costs and by those specialised in the production of intermediates, which can explain the increasing participation of Spain in global value chains. Inspection of the transmission channels suggests that the positive impact of robot adoption on exports could be driven by its positive effect on firm TFP and import probability.
Keywords: F14; O14; O33; 330; robots; firm; exports; imports; intensive margin; extensive margin; PSM; DID